2014
DOI: 10.3390/nu6093747
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Determinants of and Possible Solutions to Iron Deficiency for Young Women Living in Industrialized Countries: A Review

Abstract: Iron deficiency is a concern in both developing and developed (industrialized) countries; and young women are particularly vulnerable. This review investigates dietary determinants of and possible solutions to iron deficiency in young women living in industrialized countries. Dietary factors including ascorbic acid and an elusive factor in animal protein foods (meat; fish and poultry) enhance iron absorption; while phytic acid; soy protein; calcium and polyphenols inhibit iron absorption. However; the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
3
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 90 publications
(208 reference statements)
3
99
3
13
Order By: Relevance
“…Beck et al in UK found that 40% of women aged 19 -34 years had iron levels below the recommended levels [28]. We found 2.6% of anemic women sickle cell carriers while Al Qahtani et al reported 1.1% sickle cell disease among pregnant Saudi women, 0.5% maternal deaths, and fetal growth restriction and stillbirths accounted for 65.6% of the perinatal mortality [14].…”
Section: Discussionmentioning
confidence: 45%
“…Beck et al in UK found that 40% of women aged 19 -34 years had iron levels below the recommended levels [28]. We found 2.6% of anemic women sickle cell carriers while Al Qahtani et al reported 1.1% sickle cell disease among pregnant Saudi women, 0.5% maternal deaths, and fetal growth restriction and stillbirths accounted for 65.6% of the perinatal mortality [14].…”
Section: Discussionmentioning
confidence: 45%
“…They provided significant amounts of phosphorous and iron covering up to 15% of RNI. Although the chemical form of iron is an important factor affecting iron availability of vegetarian diets, there is no risk of iron deficiency because these diets are typically rich in vitamin C, the most significant enhancer of non-haem iron absorption (34). In relation to vitamins, a mean portion of these products provided an important source of vitamins of the B group, particularly B1 (54.4% of RNI), B12 (44.3% of RNI) and B9 (36.2% of RNI), and vitamin E (40.6% of RNI).…”
Section: Meat Analog Productsmentioning
confidence: 99%
“…Consumption of Zinc biofortified foods resulted in the amount of zinc absorbed in the diets of the subjects [31][32][33]. Study [31] showed that zinc absorbed from fortified food did not differ significantly from that observed from zinc biofortified crops.…”
Section: Discussionmentioning
confidence: 96%
“…The percentage of iron absorption from the diet generally increases with decrease in the iron stores [6]. In as much as the concentration of the iron differed in the staple crops that were used and that the feeding time periods were different, there was significant improvement in the iron status level of the subjects [33]. This shows that breeding of high iron staple crops such as pearl millet and common beans can help alleviate the prevalence of IDA which is commonly caused by inadequate intake of iron rich foods, particularly in populations from developing countries.…”
Section: Discussionmentioning
confidence: 99%